2017
DOI: 10.1016/j.jweia.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of k-epsilon turbulence model for CFD simulation of atmospheric boundary layer around a high-rise building using stochastic optimization and Monte Carlo Sampling technique

Abstract: The accuracy of the computational fluid dynamics (CFD) to model the airflow around the buildings in the atmospheric boundary layer (ABL) is directly linked to the utilized turbulence model. Despite the popularity and their low computational cost, the current Reynolds Averaged Navier-Stokes (RANS) models cannot accurately resolve the wake regions behind the buildings. The default values of the RANS models' closure coefficients in CFD tools such as ANSYS CFX, ANSYS FLUENT, PHOENIX, and STAR CCM+ are mainly adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…As mentioned in the introduction, the choice of a turbulence model has a major impact on the estimation of the turbulence scale of the flow around the evaporators. The RANS turbulence models, such as the realisable k-ε model applied in the present study, generally overestimate the wake region behind buildings, as summarised by Shirzadi et al [28]. The prediction of the RANS simulation can be improved by changing the semi-empirical coefficients of the turbulence models.…”
mentioning
confidence: 52%
“…As mentioned in the introduction, the choice of a turbulence model has a major impact on the estimation of the turbulence scale of the flow around the evaporators. The RANS turbulence models, such as the realisable k-ε model applied in the present study, generally overestimate the wake region behind buildings, as summarised by Shirzadi et al [28]. The prediction of the RANS simulation can be improved by changing the semi-empirical coefficients of the turbulence models.…”
mentioning
confidence: 52%
“…The commercial CFD code Ansys Fluent 17.0 is used to solve the three-dimensional (3D) RANS equations, and closure is obtained using the standard k ε (SKE) with LK modification (Kato and Launder, 1993) with the closure coefficient proposed by Shirzadi et al (2017). These closure coefficients provide sufficient accuracy to simulate flow in the wake region.…”
Section: Methodsmentioning
confidence: 99%
“…Since many studies have already reported that the k-ε model is appropriate for flow analysis in order to simulate turbulent jets [15,22,23], our study also used the k-ε model. In this model, k and ε are expressed in their respective transport equations as follows [23,24]:…”
Section: Numerical Modelingmentioning
confidence: 99%